Use of clozapine in older Asian patients with schizophrenia between 2001 and 2009. - Yu-Tao Xiang (Public Library of Science (PLoS), 2013)
Background To date there has been no large-scale international study that examined the use of clozapine in older patients with schizophrenia. This study examined the use of clozapine and its demographic and clinical correlates in older patients with schizophrenia in East Asia during the period between 2001 and 2009. Method Information on 1,157 hospitalized patients with schizophrenia aged 50 or older in five East Asian countries and territories (China, Hong Kong, Korea, Singapore and Taiwan) was extracted from the database of the Research on Asian Psychotropic Prescription Patterns (REAP) project. Socio-demographic and clinical characteristics and prescription of psychotropic medications were recorded. Results Clozapine was prescribed for 20.6% of the pooled sample; 19.0% in 2001, 19.4% in 2004 and 22.9% in 2009. Multiple logistic regression analysis of the whole sample revealed that patients taking clozapine had a longer duration of illness, more negative symptoms and were less likely to receive first generation antipsychotic and anticholinergic drugs, but more likely to report weight gain compared to those not receiving clozapine. Compared to those in other sites, older patients in China were more likely to receive clozapine. Conclusions The prescription of clozapine for older Asian schizophrenia inpatients has remained at a stable level during the past decade. The appropriateness of use of clozapine in China needs to be further explored.